Senior casino motivation and gaming intention: an extended theory of planned behavior model - Phillips, WooMi Jo (Kansas State University, 2009)
Senior casino gaming has been appearing as a leisure activity for the senior population as well as a research topic for many researchers from various academic disciplines. Finding out important reasons or motivations for older adults spending time in casino gaming will be the one of the fundamental ways to determine their future casino patronage intention. Accordingly, this study identifies a comprehensive inventory of senior casino gaming motivations by way of an exploratory approach. Followed Churchill’s (1979) scale development procedure, the study generated a to find five distinctive senior casino gaming motivation dimensions: winning and thrill, socialization, escape, enjoyment, and curiosity. Ultimately, confirmatory factor estimates supported that the finalized measure was unidimensional, reliable, and valid while the measurement scale was parsimonious and captured various dimensions of senior casino gaming motivation. The second part of this study investigated the applicability of an extended theory of planned behavior (TPB) with motivation component attached in context of senior casino gaming behavior. Seniors’ past casino visit was also tested for a moderator effect between the major predictor variables (attitude, subjective norms, perceived behavioral control, and motivation) and seniors’ casino behavioral intention. The findings of a structural equation modeling suggested that all predictable variables of TPB had positive effects on seniors’ casino gaming intention. Among senior casino gaming motivation, ‘winning and thrill’ and ‘enjoyment’ had direct positive effects on behavioral intention. The results of metric invariance test for moderating role of past casino visit showed that there was no indication of seniors’ past casino visit having any influence on their intention to participate in casino gaming. The overall study results suggested that the proposed extended model is a useful tool to use in studying of senior casino gaming behavior. In conclusion, theoretical and practical implications of the study findings were discussed.
Keywords: Senior Casino Gaming; Gaming Motivation; Motivation Scale Development; Theory of Planned Behavior; Casino Behavioral Intention; Metric Invariance; Business Administration, Marketing (0338); Recreation (0814)